Interrupted Midline Fascial Closure to Prevent Burst Abdomen in Emergency Laparotomy: Comparison between Continuous and Interrupted closure - Islam, Baharul; Islam, Saiful; Roy, Subroto Kumar; Alam, Nur Kutubul; Rahman, Tahmidur; Sarkar, Md Habibullah (TAJ: Journal of Teachers Association, 2018)
Burst abdomen represents one of the most frustrating and difficult postoperative complication that concerns every abdominal surgeon. It occurs because of various predisposing factors which can be prevented to some extend by having knowledge regarding them. Despite many years of experience, the optimal technique of laparotomy closure remains controversial. The varieties of surgical excess as well as the varieties of abdominal closure techniques are the main difficulties in the proper standardization of this procedure. In this paper a randomized prospective study was designed to compare with a interrupted and continuous technique for closing a midline abdominal fascia in emergency laparotomy. A total of 300 patients of acute abdominal condition who underwent laparotomy were randomized into two groups of 150 patients in each group. Total 22(7.33%) of 300 patients developed burst in the postoperative period. Fourteen (14) (9.33%) in continuous arms and eight (08) (5.33%) patients in interrupted arms developed burst. Burst abdomen occurring mostly 40-60 years age group with a male to female ratio of 1.68: 1. Cough, anemia, malnutrition, DM, intraperitoneal sepsis, wound infection, uremia and abdominal distension were the important predisposing factors for the incidence of burst abdomen. Interrupted suturing was associated with significantly reduced the burst abdomen when comparing with continuous closure. TAJ 2017; 30(2): 69-75